Survey of the perceptions of key stakeholders on the attributes of the South African Notifiable Diseases Surveillance System: data documentation - Benson, Frew (My University, 2016)
An original and uniquely created electronic semi-structured questionnaire was piloted and then sent out using the secure, web-based Research Electronic Data Capture (REDCap), programme hosted at the University of Witwatersrand. In addition to socio- demographic information, the questionnaire elicited information on participants’ perceptions of the NDSS( Notifiable Diseases Surveillance System) attributes of acceptability (the willingness of providers to participate in the NDSS), flexibility (adaptability to changing circumstances and needs), simplicity (ease of understanding of NDSS forms and processes), timeliness (the speed at which the provider takes the appropriate steps after an event came to her/his attention) and usefulness (whether the data contributes to outbreak response, or the prevention and control of communicable diseases or improved public health knowledge).
Availability of data and materials in this project: The supporting documentation explains the context in which the data was collected and analysed. It is essential for understanding the data. The researcher's results can only be replicated using the same process, techniques and conceptual models . This dataset is available to any scientist wishing to use them for non-commercial purposes after the author's periods of embargoed usage expires in 2026 , without breaching participant confidentiality. The data is part of an ongoing research project is on the South African National Notifiable Disease Surveillance System. The data set are being merged in the final study. To preserve this confidentiality these data is being held under access control in the Redcap secure severs. The datasets on which the conclusions of the paper rely is available but data access is restricted for ethical reason. Those wishing to access the read only , anonymised data for peer review purposes strictly are requested to request a copy of the data from the administrator by clicking on a file icon padlock: please state your reasons and credentials.
Keywords: Epidemiology; Dataset; Evaluation; Surveys and Questionnaires; Notifiable Diseases Surveillance System